Gel properties transition from mono-succinylation to cross-linking of agar by attemperation with succinic anhydride. (1st July 2022) - Xiao, Qiong; Ye, Siying; Zhang, Yonghui; Chen, Jun; Chen, Fuquan; Weng, Huifen; Xiao, Anfeng
Graphical abstract: Highlights: The transition from succinylation to crosslink of agar was achieved by attemperation. Agar succinylation greatly improved its swelling ratio and freeze–thaw stability. Cross-linking endowed agar with a higher gel strength and gel transparency. Abstract: Chemical modification is often used to improve the gel properties of agar but inevitably weakens gel strength in practical applications. This study achieved a breakthrough in improving the gel properties of agar without reducing its gel strength through modification with succinic anhydride. Fourier transform infrared spectroscopy and carbon nuclear magnetic resonance analyses showed that succinic anhydride could be mono-succinylated, cross-linked, and desulfurized with agar. The transition from mono-succinylation to cross-linking of agar was achieved by attemperation. Interestingly, the gel transparency of mono-succinylated agar increased from 55% to 89%, but its gel strength remarkably decreased from 1073 g/cm 2 to 188 g/cm 2 . Cross-linking endowed agar with a higher gel strength (815 g/cm 2 ) and gel transparency (85.3%). Agar succinylation demonstrated more beneficial effects and further enhanced the water-retention capacity of agar powder (18.1 g/g), the swelling ratio of agar film (1736.2%), and the freeze–thaw stability of agar gel (30.3%, 7th).